Understanding longitudinal degradation mechanisms of large-area micro-tubular solid oxide fuel cells. (1st March 2018) - Slodczyk, Aneta; Torrell, Marc; Hornés, Aitor; Morata, Alex; Kendall, Kevin; Tarancón, Albert
Abstract: The degradation mechanism of micro-tubular Solid oxide fuel cells (mSOFC) has been studied as a function of the fuel utilization (FU from 40 to 80%) along the tube (inlet, center and outlet). La0.6 Sr0.4 Co0.5 Fe0.5 O3 /Sm0.2 Ce0.8 O2 /8YSZ/Ni-YSZ pristine cells undergone to different galvanostatic tests were carefully characterized by Raman spectroscopy as well as scanning electron microscopy and energy dispersive X-ray spectroscopy analyses. In this work, remarkable cation diffusion through the barrier layer – electrolyte interface and Ni-reoxidation have been detected as main degradation mechanisms. These phenomena, strongly enhanced by the high fuel utilization, promote Y-segregation through electrolyte and anode, enhancing the reduction of the Ni-percolation paths and, eventually, leading to the reduction of the barrier layer thickness. The most significant microstructural modifications have been identified in the outlet part of the tube where especially harsh operating conditions, in terms of temperature, fuel utilization and polarization gradients, occur. An increase of the total gas flow has shown beneficial effects on the described phenomena reducing the effects of the degradation. Increasing the carrier gas flow allows lower degradation rates for cells operating under high fuel utilization up to 80% for 1000 h. Graphical abstract: Image 1 Highlights: Raman and SEM/EDX characterization of microtubular SOFC. Cationic interdifusion between barrier layer and electrolyte. Y-segregation and Ni-percolation loss in anode. Higher degradation for higher FU but protective effect of high total gas flow. Longitudinal differences in the degradation process along a microtubular SOFC.